2019
DOI: 10.1194/jlr.m093369
|View full text |Cite
|
Sign up to set email alerts
|

Lack of monoacylglycerol lipase prevents hepatic steatosis by favoring lipid storage in adipose tissue and intestinal malabsorption

Abstract: Lack of monoacylglycerol lipase prevents hepatic steatosis by favoring lipid storage in adipose tissue and intestinal malabsorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 38 publications
3
17
0
Order By: Relevance
“…First, we confirmed the resistance of Mgll −/− mice to high fat diet- (HFD-)induced obesity reported by others [ 28 , 30 , 40 ]. We observed no weight or body composition differences between WT and Mgll −/− mice at 6 weeks of age while the mice were on a standard chow diet ( Figure 1 A,C,D).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…First, we confirmed the resistance of Mgll −/− mice to high fat diet- (HFD-)induced obesity reported by others [ 28 , 30 , 40 ]. We observed no weight or body composition differences between WT and Mgll −/− mice at 6 weeks of age while the mice were on a standard chow diet ( Figure 1 A,C,D).…”
Section: Resultssupporting
confidence: 88%
“…This family is also suspected of being detrimental to cholesterol metabolism, being positively correlated with non-HDL plasma concentrations and reduced with a dietary intervention that improved cholesterol homeostasis in hamsters [ 51 ]. Interestingly, Mgll −/− mice have reduced cholesterol levels when fed a HFD as compared to controls [ 28 ] (though others have reported only trends in a western diet) [ 40 ], which one could speculate may be related in part to decreased Coriobacteriaceae levels. However, the idea that Coriobacteriaceae may regulate cholesterol metabolism is still controversial, as there is also evidence that improved cholesterol metabolism related to increased biliary cholesterol excretion results in deceases in Coriobacteriaceae as well as Erysipelotrichaceae levels [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…MGL-KO mice accumulate different MAG species in various tissues and are resistant to diet-induced obesity and protected from the development of liver steatosis [179][180][181]. In addition to its role within the lipolytic cascade, MGL is particularly important in the endocannabinoid system.…”
Section: Mgl and Its Interaction Partnersmentioning
confidence: 99%
“…Further studies showed that when Mgl -/- animals were challenged with high fat diet feeding, great amounts of 2-AG were detected in the brain, although affecting neither food consumption nor body weight, therefore evidencing cannabinoid receptors desensitizing effects[ 23 ]. Notably, the liver content of certain species of saturated and unsaturated MGs were highly enriched in Mgl -/- , showing after 12 wk high fat diet better insulin sensitivity and glucose tolerance[ 31 , 32 ]; although whether adipose depots or skeletal muscle were the main players in determining this phenotype, was not thoroughly investigated. Several other works evidenced a role of MGL in tumor growth/metabolism as well as oncogenic signaling[ 33 ], being associated with gastrointestinal stromal tumors[ 34 ] and hepatocellular carcinoma (HCC); others instead showed that MGL deletion resulted into significant colorectal cancer growth inhibition[ 35 ] while also reducing ischemia/reperfusion-induced lung injury and inflammation[ 36 , 37 ].…”
Section: Pre-clinical Studies On Monoacylglycerol Lipase Deletion/inhmentioning
confidence: 99%